Islamic Service Ethics and Organizational Culture on Service Quality and Taxpayer Satisfaction - Muhammad Akob; Rezki Arianty Akob; Gazali Amin (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
The purpose of this study is to analyze Islamic Service Ethics and Organizational Culture on Service Quality and Taxpayer Satisfaction at the Office of the Wajo Samsat Revenue Technical Implementation Unit. This study uses a quantitative approach (Quantitative approach), performs data analysis procedures with statistical equipment and aims to test hypotheses. Between one variable and another or how a variable affects other variables through hypothesis testing. This data is directly obtained from field research through direct observation of the object to be studied through data collection techniques in the form of interviews, questionnaires, and observations. In this study, the population selected were all 4-wheeled vehicle taxpayers in Samsat, Wajo district. Based on the data that has been collected and hypothesis testing with Smartpls. The results showed that Islamic service ethics had a positive and significant effect on service quality. Organizational culture has a negative and significant effect on service quality. Islamic service ethics have a positive and significant effect on taxpayer satisfaction. Organizational culture has a negative and significant effect on taxpayer satisfaction. Service quality has a positive and significant effect on taxpayer satisfaction. Islamic service ethics have a positive and significant effect on taxpayer satisfaction through service quality. Organizational culture has a negative and significant effect on taxpayer satisfaction through service quality.